South–North collaboration and service enhancements at Makerere and Bergen University libraries - Musoke, Maria G. N.; Landøy, and Ane (African Minds, 2016)
Collaboration between Makerere University in Uganda and the University of Bergen in Norway began in 1999. In 2009, the two universities celebrated the first ten years of their ongoing relationship, which includes research collaboration, scientific competence-building, student and staff exchanges, and institutional development (Musoke and Landoy 2014). The relationship also extends to the libraries at the two universities, and the collaboration between Makerere University Library (Maklib) and the University of Bergen Library (UOBL) is the focus of this chapter, although their partnership has gradually expanded to draw in libraries at other universities in Uganda, Norway and South Sudan.
Keywords: Collaboration; Service enhancement; Makerere; Bergen University libraries